Implementasi Pendidikan Kecakapan Hidup Berbasis Digital melalui Pelatihan Desain Logo Produk dan Branding Produk UMKM Bagi Ibu- ibu di Desa Panca Mukti - Ulfasari, Nia; Yunita, Wiwin; Ramadhani, Putri (Unri Conference Series: Community Engagement, 2025)
Digital-based Life Skills Education is a strategic approach to empower MSMEs (Micro, Small, and Medium Enterprises) in facing the challenges of the digital economy. This community service program aimed to enhance the skills of women MSME actors in Panca Mukti, Kabupaten Bengkulu Tengah, Provinsi Bengkulu Village in creating product visual identity through training on logo and packaging design using the Canva application. The implementation methods included demonstration, learning by doing, and coaching to ensure participants' understanding and practical skills. The training results showed a significant improvement in participants' ability to design logos that reflected their product's character and create attractive, professional packaging. Participants also developed a greater awareness of the importance of branding as a marketing strategy. Program evaluation revealed that the training was highly applicable and beneficial, boosting participants' confidence in marketing their products. It is concluded that the implementation of digital-based life skills education with participatory methods is effective in enhancing the competitiveness of MSMEs. For sustainability, further training and continuous mentoring in digital marketing and business management are recommended.